Olefins from biomass feedstocks: catalytic ester decarbonylation and tandem Heck-type coupling1. Issue 13 (14th February 2015) - John, Alex; Hogan, Levi T.; Hillmyer, Marc A.; Tolman, William B.
<x xml:space="preserve">Abstract</x> Catalytic method employs "masked" carboxylic acids to yield alkenes, via decarbonylation and/or C–C coupling of activated esters.